(untitled) (Eurasian Journal of Learning and Academic Teaching, 2023)
When studying the history of the Uzbek SSR, first of all, it is permissible to cover the history of the higher education system. In such a process, the materials of historiography and source studies are extremely important. In particular, the opening of higher educational institutions training pedagogues in the Uzbek SSR and the usefulness of specialists trained in these institutions in the central educational system proved to be in the 20s of the last century. During this period, the personnel of the field of education, who have matured in Uzbekistan, were able to show their potential, as in the entire territory of the union. This article describes the historiography of the history of educational institutions established in the Uzbek SSR and the effectiveness of their graduates.